A cross-sectional analysis of respiratory ill-health among charcoal workers and its implications for strengthening occupational health services in southern Nigeria. Issue 1 (24th January 2019) - Obiebi, Irikefe Paul; Oyibo, Patrick Gold
Abstract : Objectives: This study was conducted to assess the concentration of air pollutants at charcoal sites, the dose-response relationship between site-based exposure levels to air pollutants and prevalence of respiratory symptoms among charcoal workers, and the measures these workers employ to safeguard their health. Design: Cross-sectional but comparative design Setting: Charcoal production kiln sites in Sapele, Delta State, Nigeria. Participants: Overall 296 charcoal workers and age-matched, sex-matched and height-matched non-exposed traders (comparison group). Primary and secondary outcome measures: The primary outcome measure was the prevalence of respiratory symptoms among charcoal workers while secondary outcomes included lung function indices as well as hazard control practices among charcoal workers. Results: Majority (83.3%) of the sites had PM10 and PM2.5 values five times higher than the WHO standard. Charcoal workers were more likely to have respiratory symptoms; wheeze was statistically significant after adjusting for confounders, (OR 4.22; CI 1.37 to 12.99). The dose-response relationship between site-based exposure levels to air pollutants and the prevalence of respiratory symptoms among charcoal workers was statistically significant for all symptoms except chest tightness (p=0.167). Mean forced expiratory volume in the first second (FEV1 ) and forced vital capacity (FVC) were considerably lower among workers with differences of −0.22 (−0.42 to −0.05) L and −0.52 (-0.76 to −0.29) L, respectively, whereas FEV1 /FVC ratio and peak expiratory flow rate were higher among workers with mean differences of 5.68 (3.59–8.82)% and 0.31 (-23.70 to 24.43) L/min, respectively; but the mean difference was significant only for the FEV1 /FVC ratio. Charcoal workers had poor hazard control practices; only 3.4% reportedly used personal protective equipment. Conclusion: Air pollutants at kiln sites were higher than WHO standards. Despite the significantly higher prevalence of wheeze, chest tightness and chronic cough among charcoal workers, their hazard control practices were inadequate. Charcoal workers should adopt appropriate hazard control practices, and use improved devices which emit minimal pollutants.